COMMUNITY PARTICIPATION IN PLANNING FOR THE CONSTRUCTION OF THE TAQWA MUHAMMADIYAH MOSQUE IN GOSONG TELAGA, NORTH SINGKIL DISTRICT, ACEH SINGKIL DISTRICT - Firja Endriza (Universitas 17 Agustus 1945 Surabaya, 2023)
Community participation is very important in realizing the construction of the Taqwa Muhammadiyah Mosque so that the development planning can be felt by every level of society. The development carried out in Gosong Telaga, North Singkil District, Aceh Singkil Regency, is currently progressing well. This can be seen from the contribution of community participation in the development planning process, where the development carried out has responded to community needs. Considering the importance of community participation in the development planning process, it is necessary to study efforts to increase community participation in Gosong Telaga, North Singkil District, Aceh Singkil Regency to realize the construction of the Taqwa Muhammadiyah Mosque. This study aims to identify the form and level of community participation in the development planning process. By using the descriptive analysis method, the results showed that the community participation in the Aceh Singkil Gosong Telaga Timur Village in the Gosong Telaga community in the construction of the Taqwa Muhammadiyah Mosque was very enthusiastic, especially in the construction of the Taqwa Mosque which was carried out using a development approach with the spirit of locality.